Tolerance analysis of mechanical parts - Kondić, Živko (Array, 2020)
The determination of tolerances has a huge impact on the price and quality of products. The objective of tolerance analysis is to provide the widest possible tolerance range of parts, without disturbing the functionality of the assembly. Tolerance analysis should be performed during the design process because then there is still the possibility for change. For the purpose of carrying out the analysis, three methods will be used: Worst Case method, Root Sum Square method and Monte Carlo Simulation. Methods are explained through simple examples and applied on the one-way clutch.